Teacher Questions: Mediated-Learning Behaviors Involved in Teacher-Student Interaction During Whole-Class Instruction in Chinese English Classrooms - Liu, Huifang; Gillies, Robyn M. (Frontiers in Education, 2021)
Teacher questions have long been considered important in mediating students’ learning in language classrooms. This paper examined English teacher mediated-learning behaviors in teacher-student interaction during whole–class instruction in high schools of China. Five lessons on different topics were observed. The conversation analytic (CA) approach was applied to analyze teachers’ verbal interactions with students during whole-class teaching. Teachers’ questions and students’ responses were transcribed and categorized as display questions or referential questions. The mediated-learning behaviors involved in the two types of questions were discussed by presenting six sessions of interaction. The study investigated which question type initiated the interaction involving a more variety of mediated-learning behaviors and what pedagogical implications this may have for teacher questioning techniques that enhance student learning. The study finds the interactions initiated by referential questions contain more varieties of mediated-learning behaviors.